THE ROLE OF FINANCIAL RESOURCES IN ENSURING CORPORATE FINANCIAL STABILITY - J Alhindi, Amnah Saeed («YANGI O’ZBEKISTON IQTISODIYOTI», 2026)
Financial stability is a fundamental condition for sustainable corporate development in a volatile economic environment. Efficient formation and utilization of financial resources enable firms to maintain solvency, manage financial risks, and enhance long-term competitiveness. This study examines the role of financial resources in ensuring corporate financial stability using financial ratio analysis and comparative methods. The results show that rational allocation of financial resources improves liquidity, solvency, and profitability, thereby strengthening financial stability and reducing firms’ vulnerability to economic shocks.